Kounis syndrome leading to triple-vessel coronary artery ischaemia due to simultaneous coronary spasm, plaque erosion, and multiple stent thrombosis: a case report. Issue 5 (9th May 2022) - Yamamoto, Hiroyuki; Otake, Hiromasa; Tanimura, Kosuke; Hirata, Ken-ichi
Abstract: Background: Kounis syndrome (KS) is an acute coronary syndrome (ACS) induced by allergic reactions. Currently, there are three variants of KS based on the mechanism and onset of ACS. We report a rare case of KS, wherein ACS was caused by all KS variants. Case summary: A 68-year-old man with a history of percutaneous coronary intervention (PCI) for ST-segment elevation myocardial infarction of the left anterior descending artery 16 days ago underwent a staged PCI for the mid-left circumflex artery (LCx) stenosis under optical coherence tomography (OCT) guidance using low-molecular-weight dextran (LMWD). During OCT examination, the LMWD induced an anaphylactic reaction. The patient was immediately administered medications to manage the anaphylaxis; however, he complained of chest discomfort. Coronary angiography and subsequent intravascular ultrasound revealed a newly developed coronary thrombus in the proximal LCx. Furthermore, coronary spasm or multiple stent thromboses occurred sequentially in all coronary arteries, resulting in triple-vessel coronary artery ischaemia. Balloon angioplasty was performed under intra-aortic balloon pumping, which could rescue the patient. The patient was discharged without any complications 11 days post-KS, under a 7-day anti-histamine regimen. No further cardiovascular events had occurred by 1-year follow-up. Discussion: This case documented the clinical course of KS caused by LMWD, wherein all KS variants occurred sequentially. Early recognition of KS and appropriate management with anaphylaxis medication and balloon angioplasty under mechanical circulatory support effectively prevent vascular morbidity. Interventionalists should be aware of this rare and serious complication of PCI.